Kompetensi Bidan Puskesmas dalam Meningkatkan Pelayanan Antenatal (Studi Kasus di Puskesmas Tambak Rejo, Surabaya) - Andy Asmara (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2019)
The daily facts indicated that an individual is the key factor to achieve organization’s success. Every organization with its best performance is always related to its human resources’ balanced competency. The midwife has role, function, and competencies to provide maternal services for women. The midwife’s role is not only a doer, but also an organizer, an educator, and a researcher. Therefore, the midwife is expected to focus on prevention and health promotion aspect with basis of partnership, and community empowerment collaboration with other health workers in order to be readily prepare the health services for anyone who is in need.This was qualitative research method with case study approach. The informant was the midwives of Tambakrejo Community Health Center of Surabaya. According to the data of antenatal care attendance, trained birth attendance, and perinatal care, there were 859 pregnant women, 581 persons on phase of K1 (67.64%), and 551 persons on phase of K4 (64.14%). The birth attendances by trained birth attendants are 513 people (62.56%), while perinatal care recorded 570 people attending the health service (69.51%). The data indicated the performance by the midwives of Tambakrejo Community Health Center categorized in the lowest position among 63 community health centers in Surabaya. The result showed poor soft skill competency and poor hard skill competency on midwives. In conclusion, poor soft skill competency including personal competence and social competence should be trained and developed by obstetrics and gynecology specialist of Soewandhi Public Hospital of Surabaya. The study suggested Surabaya District Health Office needs to conduct training of technology information and computer in order to increase the service quality and to solved the problem related to hard skill competencies on technology and computer skill.